Creative Thinking Skills of Elementary School Students: Is It Still Relatively Low? - Dita Purwinda Anggrella; Indah Permatasari (JENIUS (Journal of Education Policy and Elementary Education Issues), 2023)
21st-century skills, especially creative thinking skills, are one of the skills that need to be developed starting from elementary school. Through creative thinking, you can create new ideas or ideas that are very useful as a provision for the world of work. This study aimed to diagnose creative thinking skills on indicators of fluency, flexibility, originality, and elaboration. The sample used by all populations was 53 class IV MI Muhammadiyah Gonilan students in October 2022. The exploration results showed an average of 42.45% of students at the creative level, as many as 25% at the moderately creative level, 21.70% at the non-creative level, at the less creative level as much as 9.91%, and very creative as much as 0.94%. Most students show at the creative level, and educators are expected to continue to innovate to optimize students' creative thinking skills until they can be at a very creative level